Penyuluhan Manajemen Budidaya Ikan pada Usaha Dagang di Kota Palangka Raya - Iin Nurbudiyani; Endang Sri Suyati; Santi Endriani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Management must be keen in making decisions, especially regarding sales. The purpose of this activity is to provide information to the community, especially the fish cultivations in the town of Palangka Raya on the management of fish cultivation as a material consideration in decision making in order to increase its profits. Implementation of the activities carried out by providing counseling to residents fish cultivations and a number of students who participate in these activities. Community service is implemented by budget on Year 2015. Community service was implemented during 2 (two) months and the providing counseling implemented one fullday at 07.00 pm until 17.00 pm. Activities begin with the opening, provision of material and followed by discussion and questions. The material presented in this counseling regarding information on how aquaculture, which produces high value, include; corporate management, financial management and marketing management. This activity was successfully implemented for their excellent response and high motivation of the participants as well as can be seen from the presence of ladies and gentleman and teenagers who are developing fish cultivations on the home page or in land they had prepared